2018
DOI: 10.1016/j.cdtm.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Progress in targeted therapy for breast cancer

Abstract: Breast cancer is a multistep, multifactorial, and heterogeneous disease. Significant transformations have occurred in the systemic management of breast cancer in the past decade. Due to the further understanding of pathogenesis, scientists have found plenty of signaling pathways and correspondingly therapeutic targets in breast cancer, such as hormone receptor, human epidermal growth factor receptor 2 (HER2), epidermal growth factor receptor (EGFR), vascular endothelial growth factor (VEGF), phosphoinositide-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 53 publications
0
47
0
Order By: Relevance
“…The most common cause of hereditary breast cancer is an inherited mutation in the BRCA1 or BRCA2 gene, which are tumor suppressor genes involved in such essential functions as DNA repair [87,88]. There are various biological processes and genetic mutations that lead to the appearance of breast cancer and sensitivity to various drugs, such as hormone receptor, human epidermal growth factor receptor 2 (HER2), EGF, vascular endothelial growth factor (VEGF), mechanistic target of rapamycin (mTOR), and cyclin-dependent kinase 4/6 (CDK4/6) [89]. Women, compared to men, present a 100-fold increased risk of having breast cancer; furthermore, aging and heredity also contribute as predisposing factors to the disease [88].…”
Section: Nanotheranostics In Diagnosis and Treatment Of Cancermentioning
confidence: 99%
“…The most common cause of hereditary breast cancer is an inherited mutation in the BRCA1 or BRCA2 gene, which are tumor suppressor genes involved in such essential functions as DNA repair [87,88]. There are various biological processes and genetic mutations that lead to the appearance of breast cancer and sensitivity to various drugs, such as hormone receptor, human epidermal growth factor receptor 2 (HER2), EGF, vascular endothelial growth factor (VEGF), mechanistic target of rapamycin (mTOR), and cyclin-dependent kinase 4/6 (CDK4/6) [89]. Women, compared to men, present a 100-fold increased risk of having breast cancer; furthermore, aging and heredity also contribute as predisposing factors to the disease [88].…”
Section: Nanotheranostics In Diagnosis and Treatment Of Cancermentioning
confidence: 99%
“…However, only 5% of molecules that show anticancer activity in preclinical studies are approved upon demonstration of sufficient efficacy in phase III clinical trials [90]. This trend is extremely prevalent especially for vascular endothelial growth factor (VEGF) inhibitors (e.g., Bevacizumab), which are also used for BC treatment [91]. As reported for AD [56][57][58][59][60][61], incorrect identification of drug targets, improper proposed mechanism of action, drug toxicity, drug resistance, and weak genetic evidence are among the possible failure reasons [22].…”
Section: Breast Cancermentioning
confidence: 99%
“…According to the progression in breast cancer pathogenesis, it has been found that hormonebased signaling pathways as well as their receptors are crucial in breast cancer and breast cancer-targeted hormone therapy plays an important role in clinical treatment [20]. The main receptors regarding in breast cancer are HER2, IFNɣR, TNFαR and PR.…”
Section: Diagrammentioning
confidence: 99%